THE ROLE OF CULTURAL EVENT IN A MUSEUM TO THE TOURISTS SATISFACTION AND DESTINATION LOYALTY - Ulinnuha, Hana; Wijaya, Theodora Evelyn; Alanda, Hilwa Shufia (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
Understanding tourism destination loyaly would be an invaluable benefit for tourism authorities. Especially after the pandemic, tourism authorities are working hard to revive tourism in 2022. Many tourism destinations in Indonesia are gradually implementing various activities to entice tourists to return. As one of the tourism destinations in Indonesia, Surakarta (Solo), whose branding is